2003
DOI: 10.2176/nmc.43.352
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Vertebral Metastases from Malignant Cardiac Pheochromocytoma-Case Report-

Abstract: A 27-year-old male presented with a very rare metastasis to the vertebral body from a cardiac pheochromocytoma manifesting as a pathological fracture of the C-4 vertebral body that occurred while playing golf. The patient was initially treated with hard collar fixation. Gallium scintigraphy demonstrated multiple hot spots in the mediastinum, the frontal bone, the vertebral column, and the rib. Magnetic resonance imaging of the chest delineated a cardiac tumor. The patient underwent biopsies of the cardiac and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…This could be attributed to the routine use of preoperative alpha blockade and embolization, which has been associated with decreased surgical morbidity, reduced blood loss and transfusions, and shorter hospital stays. 1,3,26,31 All 5 patients in our cohort received alpha blockade with phenoxybenzamine with or without metyrosine for at least 2 weeks prior to surgery, and 3 underwent preoperative embolization. None of the patients experienced intraoperative hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the routine use of preoperative alpha blockade and embolization, which has been associated with decreased surgical morbidity, reduced blood loss and transfusions, and shorter hospital stays. 1,3,26,31 All 5 patients in our cohort received alpha blockade with phenoxybenzamine with or without metyrosine for at least 2 weeks prior to surgery, and 3 underwent preoperative embolization. None of the patients experienced intraoperative hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant forms account for 10%-20% of all cases and most commonly metastasize to the liver, lymph nodes, spleen, and lungs. 4,14,31,32 Five-year survival rates range from 84% to 96% for benign pheochromocytoma, to less than 50% for malignant pheochromocytoma. 7,27,30 Although bony involvement and skeletal spread are well-described complications of malignant pheochromocytoma, the spine is a relatively uncommon site of metastasis.…”
mentioning
confidence: 99%
“…On reviewing the international medical literature in English (including case reports and reviews) obtained from electronic databases on paragangliomas, we found only 7 reports [15,16,17,18,19,20,21] mentioning paraganglioma involving cervical spine (table 1). Blades et al [15] reported a patient with primary paraganglioma involving the cervical spine who later developed multiple intracranial and spinal metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…악성의 경우는 천천히 자라는 특징이 있고, 뼈(50%), 간(50%), 그리고 폐(30%) 등으로 전이된다 [5,6]. 뼈 전이를 일으킨 경우에는 통증 과 신경압박을 유발할 수 있고 이와 연관된 증상이 나타나는데 [7], 척추 전이는 매우 드물게 발생한다 [8]. …”
Section: 척추와 대동맥주위 림프절로 전이한 거대 갈색세포종unclassified